2014
DOI: 10.7785/tcrt.2012.500380
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Dosimetric Assessment by Cone-Beam Computed Tomography Scans in Head and Neck Radiation Therapy: A Monitoring in Four Phases of Treatment

Abstract: Due to the anatomical changes frequently occurring during the course of head and neck (H&N) cancer radiotherapy, the dose distribution, which was actually delivered to the patient, might significantly differ from that planned. The aim of this paper is to investigate these volumetric changes and the resulting dosimetric implications on organs at risk (OARs) and clini- and 25 th CBCT (13.3%) but it complied with dose constraint. The differences observed for the spinal cord and mandible maximum doses were not cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Clear swelling of the larynx and pharyngeal constrictor muscles was found by Ricchetti et al [53] at week seven of radiotherapy. Swelling of the larynx was also reported by Cozzolino et al [66], five weeks after the start of radiotherapy. Popovtzer et al [52] observed a thickness change of +111% in parts of the pharyngeal constrictors that received more than 50 Gy, three months post chemoradiation.…”
Section: Other Organs At Riskmentioning
confidence: 61%
See 3 more Smart Citations
“…Clear swelling of the larynx and pharyngeal constrictor muscles was found by Ricchetti et al [53] at week seven of radiotherapy. Swelling of the larynx was also reported by Cozzolino et al [66], five weeks after the start of radiotherapy. Popovtzer et al [52] observed a thickness change of +111% in parts of the pharyngeal constrictors that received more than 50 Gy, three months post chemoradiation.…”
Section: Other Organs At Riskmentioning
confidence: 61%
“…Sanguineti et al [62] studied weekly CT scans of eighty-five patients and concluded that the PG shrinkage is not linear (PGs shrunk most during the first half of treatment). Thirty-eight papers reported on PG anatomic changes [2,4,6,7,9,12,13,[15][16][17][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]47,48,50,53,56,57,59,60,[62][63][64][65][66]. The most common reported anatomic changes were volume loss (Table S1) and medial shifts of the PGs [17,[32][33][34]37,42,44,45,48,51,...…”
Section: Parotid Glandmentioning
confidence: 93%
See 2 more Smart Citations
“…While some of the patients had 95% or 93% isodose line shifts less than 1 mm due to 1 cm uniform body contour change, some of the patients had 95% or 93% isodose line shifts more than 4 mm. This may explain the fact that although there was literature claiming the target coverage was affected by anatomical changes (e.g., weight loss), others showed that anatomical changes had minimal effect on target coverage …”
Section: Resultsmentioning
confidence: 99%